신발디자인 특성에 따른 경증 족부질환 환자의 정형 신발 구매의 의도와 만족도 영향 분석 - 박준홍(Junhong Park); 이준상(Junsang Lee) (한국정보통신학회논문지, 2022)
In recent years, the number of foot disease patients due to bad walking habits and living environment is increasing. We examine how patients with mild foot disease according to shoe design characteristics affect satisfaction and purchase intention when purchasing orthopedic shoes. The design characteristics of shoes consisted of functionality, convenience, and aesthetics. It was found that aesthetics had an effect on purchasing orthopedic shoes. Even if the factors of functionality and convenience have little effect, if the aesthetic is high, purchase intention and satisfaction are affected. Various elements are required for design according to the frequency of participation in social activities for each mild foot disease and the purpose of wearing it. It is expected that the development of useful orthopedic shoe designs that patients with mild foot disease can wear in their daily life will lead to practical application and satisfaction by further supplementing the characteristic factors of orthopedic shoe design identified through the research results. 최근 들어 잘못된 보행 습관과 생활환경으로 인한 족부 질환자들이 늘어나고 있다. 신발디자인 특성에 따른 경증 족부질환 환자가 정형 신발 구매시 만족도와 구매 의도에 어떠한 영향을 미치는지 살펴본다. 신발 디자인 특성은 기능성, 편의성, 심미성으로 구성하였다. 심미성이 정형 신발 구매 시 영향을 미치는 것으로 나타났다. 기능성과 편의성의 요소가 영향이 적더라도 심미성이 높다면 구매의도와 만족도에 영향을 준다. 경증 족부질환별 사회활동 참여 빈도와 착용 목적에 따라 디자인 또한 다양한 요소들이 요구된다. 연구 결과를 통해 알아본 정형 신발디자인 특성 요인을 더욱 보완하여 경증 족부질환 환자들이 일상생활에서 착용할 수 있는 유용한 정형 신발 디자인 개발과 현실적인 활용과 만족으로 이어지길 기대한다.